Social capital and institutions. A tentative analysis of the polish case - Andrzej Rychard (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2006)
The article deals with the relationship between social capital and institutional system in post-communist Poland. In the first part the author presents the factors contributing to a social fragmentation (and integration) in post-communist and “post-solidarity” Poland. One of the theses shows that these factors should be seen in historical and evolutionary perspective and that even in the beginning of the Solidarity period there have been already seeds of disintegration built into the system. In the second part some empirical illustrations concerning networks of social capital of trust are presented. The author attempts to show the peculiarities of the relationship between the level of interpersonal trust and some aspects of the institutional performance, including the economic one. The concluding part deals with the discrepancies and similarities in the trust level concerning local and European politicians in various European countries.
Keywords: 300